Pesantren Online: Pergeseran Otoritas Keagamaan di Dunia Maya - Qudsy, Saifuddin Zuhri (Living Islam: Journal of Islamic Discourses, 2019)
The cyberspace has been causing disruption in various aspecs of people's lives and institutions, including pesantren. This oldest religious institution in Indonesia has also redefined its meaning, thereby constructing a new stream called "Pesantren Online" (online Islamic school) which changes people's perception of the Pesantren itself. As a means of religious learning, Pesantren Online, in this case, the site www.pesantrenvirtual.com, tries to satisfy the public's desire for religious matters. This paper concludes that the human need to obtain information on religious themes has instantly triggered the creation of religious online sites, such as pesantrenvirtual.com, as a reference to resolve the confusion of religious surfers.